Gestão social do desenvolvimento: a exclusão dos representantes dos empresários? o caso do programa Territórios da Cidadania norte-RJ - Zani, Felipe Barbosa (2010)
The incorporation of the territorial approach as the basis of rural development policies led to, among other advances, the break with centered vertical tradition of development strategies, and the consequent importance of local initiatives and actors. This approach accepts the social management and its principles of inclusion, concerning the incorporation of the players excluded from decision-making process, and pluralism, regards to the multiplicity of actors in decision-making about public policy. In Brazil, the territorial approach is embraced by the Programa de Desenvolvimento Sustentável dos Territórios Rurais and its successor, the Programa Territórios da Cidadania. However, the trajectory of rural development policies is eminently rural for it focuses on organizations linked to family farming and excludes organizations representing employees, despite the principles ported by social management and the adoption of a territorial approach, that should involve the mobilization of social dynamics present in the territories. Thus, considering the significance of business participation for the success of such policies, this work examines the possibilities of including representatives of entrepreneurs to pluralism within the Programa Territórios da Cidadania. In this case study we chose to understand the dynamics of the Program in the North Region of Rio de Janeiro State, where representatives of civil society, businessmen, SEBRAE and members of the Ministério do Desenvolvimento Agrário were interviewed. The study was supplemented by documentary analysis, and treated by analysis of content with combined graph developed based on the habermasian concept of deliberative citizenship. The results reveal that business representatives are not included in the territorial collegiate North-RJ, and neither know the Programa Territórios da Cidadania. The civil society groups, who consider the collegiate as a Family Farming Forum, reject indistinctly the inclusion of entrepreneurs because of socio-political differences, compounded by the political history of the region. Pluralism is also encumbered by the processes used in the formation of the territory, in the composition of the collegiate body and in the preparation and evaluation of projects. The business representatives, in turn, are already included in other instances of social participation, such as municipal councils of public policies, and accept the dynamics that governs these spaces lined on substantive rationality. Its insertion can be facilitated by SEBRAE/RJ, which has a good reputation among entrepreneurs and has also fostered the articulation of territorial actors. Despite the possibilities for inclusion, the actual model of social management is not capable of promoting the social concertation of the dynamic forces for the development of the North region of Rio de Janeiro State.